Indimap: Ferramenta integrada para monitoramento de desmatamento e queimadas em terras indígenas - Miranda, José Mario Fraga; Negócio, Yuri Feitosa; Marques, Juan Cassio O.; Brito, Samara da Silva; Pessoa, Diego Ernesto Rosa (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2023)
Indigenous lands offer a significant solution for preserving Brazilian forests, particularly amidst the alarming rise in deforestation driven by weakened environmental control policies. Recent data from the Amazon Environmental Research Institute (IPAM) reveals a disturbing 153% increase in deforestation on indigenous lands. To address this pressing issue, we present "INDIMAP," a public platform designed for civil society to monitor illicit deforestation events on indigenous territories. By utilizing publicly available databases from INPE, MAPBIOMAS, and DETER, the platform systematically identifies and disseminates deforestation information through a user-friendly portal and social media channels. This initiative aims to enhance visibility and comprehension of deforestation data, empowering civil society to advocate for positive changes and combat deforestation growth effectively. The success of INDIMAP holds the potential to safeguard Brazilian forests and foster sustainability for future generations.